2014
DOI: 10.1590/s0100-204x2014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Estirpes de Bradyrhizobium em simbiose com guandu-anão em casa de vegetação e no campo

Abstract: Resumo -O objetivo deste trabalho foi avaliar a eficiência simbiótica de estirpes de bactérias fixadoras de nitrogênio do gênero Bradyrhizobium com guandu-anão. Os experimentos foram conduzidos em vasos de Leonard, em vasos com solo e em campo. Foram testadas 11 estirpes em vasos de Leonard, e as que apresentaram maior eficiência em promover o crescimento do guandu-anão foram avaliadas em vasos com solo (Latossolo Vermelho-Amarelo e Cambissolo) e em campo (Latossolo Vermelho-Amarelo). Em todos os experimentos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…By testing these same treatments in dwarf pigeon pea 'Iapar 43' (Aratã), Rufini et al (2014b) observed that the strain UFLA 03-320 also stood out, as was the case in this study. Thus, since it was effective in forming symbiosis with different cultivars, it can be recommended for this species.…”
Section: Evaluation Of Efficiency In the Fieldsupporting
confidence: 72%
See 2 more Smart Citations
“…By testing these same treatments in dwarf pigeon pea 'Iapar 43' (Aratã), Rufini et al (2014b) observed that the strain UFLA 03-320 also stood out, as was the case in this study. Thus, since it was effective in forming symbiosis with different cultivars, it can be recommended for this species.…”
Section: Evaluation Of Efficiency In the Fieldsupporting
confidence: 72%
“…is a Fabaceae that benefits from BNF, obtaining most of the N required for its development from this process. This was confirmed by experiments in axenic conditions (Fernandes and Fernandes, 2000;Fernandes et al, 2003;Martins et al, 2012), in pots with soil (La Favre and Focht, 1983;Valarini and Godoy, 1994;Sanginga et al, 1996;Paz et al, 2000), or under field conditions (Espanã et al, 2006;Ahmed et al, 2014;Rufini et al, 2014b). This crop can be used for several purposes, such as for green manure (Heinrichs et al, 2005), animal feed, and human consumption (Mizubuti et al, 1995;Canniatti-Brazaca et al, 1996); for phytoremediation (Pires et al, 2006); and for recovery of degraded areas (Beltrame and Rodrigues, 2007).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies with an important cultivar of dwarf pigeon pea (IAPAR 43, Aratã) focusing on aspects related to crop rotation (Ferrari Neto et al 2012), soil compaction (Farias et al 2013), influence on soil characteristics (Cardoso et al 2014), and nitrogen fixation (Rufini et al 2014) showed promising characteristics of this pea. Dwarf pigeon pea's fresh matter of 23.80 t•ha -1 at 92 days after sowing demonstrates its potential as a cover crop (Pereira et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of inoculant strains has been consolidated in soybeans, it is important to consider that these microorganisms can be significantly influenced by several factors, such as climatic conditions, pH, nutrient availability, humidity, soil texture, and competition with the native communities of N 2 -fixing bacteria (rhizobia) for the occupation of infection sites in the roots of the host plants (Kaschuk et al, 2016;Castro et al, 2017;Thilakarathna & Raizada, 2017). However, there may be strains with desirable symbiotic characteristics for selection in these autochthonous communities, which can be used as inoculants of soybeans (Rufini et al, 2014;Ribeiro et al, 2015;Bromfield et al, 2017;Chibeba et al, 2017). These facts reinforce the need for recurrent selection of new efficient Bradyrhizobium strains.…”
Section: Introductionmentioning
confidence: 99%